Favorable Outcomes of Revision Hip Arthroscopy Irrespective of Whether Index Surgery was Performed by the Same Surgeon or a Different Surgeon. (9th December 2021) - Ankem, Hari K.; Diulus, Samantha C.; Kyin, Cynthia; Jimenez, Andrew E.; Maldonado, David R.; Sabetian, Payam W.; Saks, Benjamin R.; Lall, Ajay C.; Domb, Benjamin G.
Abstract : Introduction: The purpose of this study was to compare minimum 2-year patient-reported outcomes (PROMs) after revision hip arthroscopy between two different patient cohorts who had undergone primary hip arthroscopy with the same surgeon (SS) and a different surgeon (DS). We hypothesized no difference in clinical outcomes between the groups despite differences in intraoperative findings based on the surgical decision making in a revision setting at a high-volume center. Methods: Between January 2012 and August 2017, 71 SS patients were matched for age, sex, body mass index, and follow-up to 71 DS patients. Modified Harris hip score (mHHS), nonarthritic hip score, and hip outcome score—sports-specific subscale (HOS-SSS) were collected prospectively. The minimal clinically important difference was calculated for mHHS and HOS-SSS. Results: All the DS patients had labral tears, and 94.4% had femoroacetabular impingement from residual bony deformity ( P < 0.001). The SS and DS groups demonstrated significant and comparable improvement in mHHS (Δ = 18.3 ± 21.5 versus 19 ± 20.1; P = 0.837), nonarthritic hip score (Δ = 18.8 ± 18.8 versus 18.2 ± 18.8; P = 0.850), and HOS-SSS (Δ = 22 ± 27.4 versus 17.5 ± 28.1; P = 0.275). The rates of achieving minimal clinically important difference for mHHS and HOS-SSS were similar. Furthermore, the need for revision surgery and conversion to total hip arthroplasty were comparable ( P = 0.228 and P = 0.383). Conclusions: Patients undergoing revision hip arthroscopy reported notable and comparable improvement in multiple patient-reported outcomes at a minimum 2-year follow-up, irrespective of intraoperative findings or primary source of patient pool.